Legal Aid Advocacy for the Poor in Law of Welfare States - Hayatul Ismi (The Indonesian Journal of International Clinical Legal Education, 2019)
Indonesia is a lawful welfare state, which means that the government has a duty and responsibility in realizing the social justice and the general welfare of the people. Paragraph (1) of the 1945 Constitution, stated that The State must ensure the implementation of equality in the standing before the law. Nowadays it seems only the lower class that must obey the law, while the upper class seems to be immune to the law. They are hiding from the law behind the layers of their own money. As if the law can be sold using money, even for those who commit major crimes, corruption for example. While the lower classes who commit minor crimes can be imprisoned. Our country is a country of law, then the law should be enforced, for all people and not just for Reviews those who have the money. To realize the implementation of the idea of a lawful welfare state then the State should guarantee the right of every person to reach justice. In other words, the State must guarantee the implementation of legal aid to the impoverished or Reviews those who cannot afford so that none has no access to justice that is mandated by the constitution. Legal aid advocacy for the impoverished in the concept of a lawful welfare state is certainly to be important in realizing the ideals of the lawful welfare state that achieve social justice and general welfare of the people. Therefore, it is important to know the concept of advocacy suitable for the impoverished in a welfare state.